Rencana Usaha Pencucian Sepatu Shoes.co - Rahmawati, Ambar Mutia; Pertiwi, Felisa Tiara; Faiz, Faiz; Marsyeli, Indah; Rahmadinta, Nadhira Nurisa; Rattu, Nathaya Syahid; Purnita, Resta; Putra, Setiani Firmana (Journal of Entrepreneurship, Management and Industry (JEMI), 2020)
Shoes.Co are cleaning, caring for and repairing shoes using quality materials, detailed service processes and carried out by those who are experts in their fields to ensure that prospective customers get back shoes like they have just returned. The types of shoes that Shoes.Co can serve are Sneakers (Casual and Sports), types of shoes made from suede and shoes with leather or leather.